Nutritional Evaluation of Sago of Gebang Tree (Corypha utan Lamk) from Different Locations in West Timor - Indonesia for Broilers - C. L. Nalle; Helda Helda; B. Masus; J. Malo (Faculty of Animal Science, Bogor Agricultural University, 2021)
Two experiments were conducted to evaluate the nutritional value of sago from different locations in West Timor, Indonesia for broilers. Experiment I aimed at determining the apparent metabolizable energy (AME) and nutrient digestibility of sago from different locations. A total of 120 broilers (unsexed, age 21 d) were randomly distributed to 24 metabolic cages (5 birds/cage). The experimental design was a completely randomized design (CRD) consisting of 6 treatments and 4 replications. The experimental diets were a basal diet (maize-soy) and 5 treatment diets which were a mixture of basal ration (75%) and sago (25%) from different locations. Experiment II was about performance trials. Two different basal diets were formulated, supplemented with synbiotics and fed to 200 birds (unsexed, 10 birds/pen). The experimental design was a 2 x 2 factorial CRD. With the exception of phytate and phenol contents, the results showed that the location affected (p<0.05 to 0.01) the contents of dry matter, crude protein, and crude fiber, tannins, NDF, ADF, flavonoids, AME/n, and starch digestibility of sago. The location did not affect (p>0.05) ash, crude fat, starch, Ca, P, and gross energy contents of sago. Basal diets affected (p<0.05 to 0.001) all performance traits. Except for BWG, synbiotics did not affect (p>0.05) the performance of the birds. In conclusion, the nutrient composition and digestibility of sago are affected by locations. Sago is rich in starch and high in AME values, but poor sources of calcium, phosphor, and protein. Sago contains fiber, tannin, phytate, flavonoids, and phenol. Sago diets improved the performance of broilers. Synbiotics did not improve the performance of birds.